2001
DOI: 10.1359/jbmr.2001.16.1.135
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C Supplement Use and Bone Mineral Density in Postmenopausal Women

Abstract: Vitamin C is known to stimulate procollagen, enhance collagen synthesis, and stimulate alkaline phosphatase activity, a marker for osteoblast formation. Studies of dietary vitamin C intake and the relation with bone mineral density (BMD) have been conflicting, probably because of the well-known limitations of dietary nutrient assessment questionnaires. The purpose of this study was to evaluate the independent relation of daily vitamin C supplement use with BMD in a population-based sample of postmenopausal wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
0
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(103 citation statements)
references
References 17 publications
3
96
0
4
Order By: Relevance
“…Thus fibrils or/and the structure may disintegrate rapidly. Our findings were also supported by Simon et al [21], and Morton et al [22]. Table 1 shows that after therapy, no significant change occurred in vitamin C level in PMO.…”
Section: Resultssupporting
confidence: 90%
“…Thus fibrils or/and the structure may disintegrate rapidly. Our findings were also supported by Simon et al [21], and Morton et al [22]. Table 1 shows that after therapy, no significant change occurred in vitamin C level in PMO.…”
Section: Resultssupporting
confidence: 90%
“…Vitamin C is required for collagen crosslinking (Combs, 1998) and along with other antioxidant vitamins may serve to protect the skeleton from oxidative stress, especially from smoking (Melhus et al, 1999). Two recent population-based studies showed that use of long-term vitamin C supplements was beneficial for BMD in various skeletal sites (Leveille et al, 1997) and the effect was augmented by estrogen and Ca supplements use (Morton et al, 2001) in postmenopausal women. In our study, the stronger influence was seen with the vitamin C from food only than total (food and supplement), probably because the supplemental intake is not regular and/or of longer duration.…”
Section: Multiple Regression Resultsmentioning
confidence: 99%
“…Moreover, some literature documents that the above alkaline-forming cations have an independent impact on improving Ca balance (31,32) and bone health (5,6,33) . The second aspect is that vegetables and fruit might affect bone health via the roles of antioxidant vitamins, such as vitamin C (34,35) and vitamin K (36,37) . However, after adjusting for the potential influence of these nutrients, vitamin D and fibre, McGartland et al (24) proved that the positive association between fruit intake and heel BMD in the 12-year-old girls remained.…”
Section: Discussionmentioning
confidence: 99%